The hazards of coastal erosion in Central Java, Indonesia: An overview - Muh Aris Marfai, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
As an archipelago country, Indonesian coastal areas are the most dynamic and strategic areas for development as they provide many resources for human livelihood. At the same time, however, coastal areas are also prone to environmental hazards such as erosion and sedimentation processes. Erosion along the coast may cause loss of coastal land and damage infrastructures and buildings. The Semarang City, Tegal Regency, and Demak Regency of the Central Java Province are especially vulnerable to coastal erosion. This paper examines both the phenomenon and mitigation of erosion hazards in Central Java. It was found that in Semarang City, for the past 100 years coastal erosion has threatened facilities and land use along the coast causing extensive loss of coastal land. The local government has embarked on several mitigating measures including the construction of dykes and sea walls. Similarly, coastal erosion and abrasion had damaged tourism infrastructures and diminished the coastal land of the Tegal Regency since 1994. In Demak it led to the relocation of settlement and damage of aquaculture. Given the significant role of the city of Semarang, Tegal and Demak in the ongoing development of Central Java the issues of coastal erosion should have garnered serious attention from local and provincial government. Needless to say, coordination between planning and implementation of mitigation measures need to be comprehensive and enhanced.